2015
DOI: 10.1037/spq0000079
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Social Skills Improvement System Classwide Intervention Program (SSIS-CIP) primary version.

Abstract: A multisite cluster randomized trial was conducted to examine the effects of the Social Skills Improvement System Classwide Intervention Program (SSIS-CIP; Elliott & Gresham, 2007) on students' classroom social behavior. The final sample included 432 students across 38 second grade classrooms. Social skills and problem behaviors were measured via the SSIS rating scale for all participants, and direct observations were completed for a subsample of participants within each classroom. Results indicated that the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 41 publications
6
40
1
1
Order By: Relevance
“…Two of these studies have reported negative results of the programmes evaluated (Lemma et al 2012;McGlowry, Snow & Tamis-LeMonda, 2005) while two studies have shown slight improvements in students emotional regulation, social communication skills, cooperation and teamwork (Holen et al 2012; Authors, forthcoming). The strongest findings of the study report improvement in social skills, cooperation, assertion, self-control and engagement (DiPerna et al, 2014).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Two of these studies have reported negative results of the programmes evaluated (Lemma et al 2012;McGlowry, Snow & Tamis-LeMonda, 2005) while two studies have shown slight improvements in students emotional regulation, social communication skills, cooperation and teamwork (Holen et al 2012; Authors, forthcoming). The strongest findings of the study report improvement in social skills, cooperation, assertion, self-control and engagement (DiPerna et al, 2014).…”
Section: Resultsmentioning
confidence: 80%
“…Five studies have rigorously evaluated the programmes and the findings are trustworthy (DiPerna et al, 2014;Holen et al, 2012;Lemma et al, 2012;McGlowry, Snow & Tamis-LeMonda, 2005; Authors, forthcoming). However, the results on improvement of the non-cognitive skills are mixed.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, recognizing and treating children with insufficient social skills is considered an important task for psychologists, advisors, and professionals in education and training (Agran et al, 2016;DiPerna, Lei, Bellinger, & Cheng, 2015).…”
Section: Responsibility Of the Conference Organization Committeementioning
confidence: 99%
“…ラムにおいても,ソーシャルスキルが積極的に取り上 げられ (Bradshaw, Waasdorp, & Leaf, 2015;DiPerna, Lei, Bellinger, & Cheng, 2015;Gresham, Elliott, Cook, Vance, & Kettler, 2010) ,子どもの態度や行動に関して,一定 の効果が維持されることが報告されている (Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, 2011 (Chen, Rubin, & Li, 1997;Dubow, Tisak, Causey, Hryshko, & Reid, 1991;Hymel, Rubin, Rowden & LeMare, 1990;前田, 1998;Wentzel, 2003) , こ れはクラス替えなどによって対人関係は変わるという 不可避な問題は存在するものの,その影響を認めた上 でも,社会的結果の予測を議論することに大きな意義 が見出されているからである。そして,ソーシャルス キルは学習によって獲得され得る対人能力であること から (Gresham, Van, & Cook, 2006 Model 9 は十分な適合度を示し (χ 2 (2) = 0.906, p = .636, CFI = 1.000, TLI =…”
unclassified